PENGEMBANGAN SISTEM PENDUKUNG KEPUTUSAN UNTUK OPTIMASI BATASAN MODAL MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS (AHP)–ABSOLUTE MEASUREMENT DAN MODEL PROTOTYPE - Imam Fauzi Muldani Rachmat; Jaka Suwita; Adiyanto (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2026)
Inventory management in small-scale retail businesses often encounters irregular stock conditions that lead to lost sales on high-demand products, dead stock on slow-moving items, and limitations in working capital. This study aims to design and develop a Decision Support System (DSS) to optimize stock replenishment at Toko Ilham, Banjar. The system was developed using the Prototype model, while priority determination employed the Analytical Hierarchy Process (AHP) for criteria weighting and the Absolute Measurement method for evaluating alternative stock items. The novelty of this research lies in the integration of AHP with a budget-constraint optimization algorithm that automatically selects purchase recommendations based on real financial capacity—an aspect not addressed in previous studies, which generally produce only ranking outputs without budget consideration. The results show that demand level is the most dominant criterion (50.5%), and the system is capable of generating precise recommendations such as full purchase, partial purchase, or deferred purchase based on the remaining budget. Black Box testing confirms that all system features function correctly, supporting store owners in making more objective and efficient restocking decisions